1988
DOI: 10.1037/0882-7974.3.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting of pictures over a long retention interval in young and older adults.

Abstract: Young and older adults were presented with pictures for study. Their recognition of the information was tested at five retention intervals: immediately, and 48 hr, 1 week, 2 weeks, and 4 weeks later. The main finding of interest was that picture recognition did not show an age-related decline until the 1-week retention interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 6 publications
4
27
0
Order By: Relevance
“…Aging in humans is associated with a weakening of working memory, executive function, and processing speed; however, the most notable decline is observed as impaired episodic memory, including spatial memory (Kukolja et al , 2009; Plancher et al , 2010; Uttl and Graf, 1993). The impairment can be identified as a mild deficit in the rapid acquisition of flexible information and an increase in the rate of forgetting (Davis et al , 2003; Hogge et al , 2008; Huppert and Kopelman, 1989; Kral, 1962; Macdonald et al , 2006; Mitchell et al , 1990; Park et al , 1988; Rajah et al , 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Aging in humans is associated with a weakening of working memory, executive function, and processing speed; however, the most notable decline is observed as impaired episodic memory, including spatial memory (Kukolja et al , 2009; Plancher et al , 2010; Uttl and Graf, 1993). The impairment can be identified as a mild deficit in the rapid acquisition of flexible information and an increase in the rate of forgetting (Davis et al , 2003; Hogge et al , 2008; Huppert and Kopelman, 1989; Kral, 1962; Macdonald et al , 2006; Mitchell et al , 1990; Park et al , 1988; Rajah et al , 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The impairments often take the form of rapid forgetting of recently learned information in both humans (Gagnon and Belleville, 2011; Huppert and Kopelman, 1989; Munro Cullum et al, 1990; Park et al, 1988) and rodents (Barnes, 1991; Countryman and Gold, 2007; Foster, 1999; Gold, 2005, 2008; Gold et al, 1982; Korol, 2002; Quartermain et al, 1988; Salinas and Gold, 2005; Winocur, 1988; Zornetzer et al, 1982). Previous work in rodents suggests that rapid forgetting may reflect deficits in neurobiological mechanisms of memory formation initiated during or soon after training.…”
Section: Introductionmentioning
confidence: 99%
“…In aging research, forgetting rates have been studied across different age groups and retention intervals and the findings are mixed. Whereas some studies reported differences in initial performance, but invariant forgetting rates in older and younger adults (Fjell et al, 2005;Rybarczyk, Hart, & Harkins, 1987;Spikman, Berg, & Deelman, 1995), others have shown greater forgetting in older adults, especially after long delays (e.g., 1 week; see Huppert & Kopelman, 1989;Park, Royal, Dudley, & Morrell, 1988), or when testing individuals on episodic recall, rather than recognition tasks (MacDonald, Stigsdotter-Neely, et al, 2006). With respect to experimental manipulations, encoding factors such as meaningfulness of the material (Underwood & Richardson, 1956), degree of learning (Slamecka & McElree, 1983), and pictorial elaboration (Forbes & Reese, 1974) have been found to affect initial rate of learning, but not rate of forgetting.…”
Section: Interindividual Differences In Forgettingmentioning
confidence: 99%